Congratulations on the publication of the first issue of Journal of Rural Tourism - Ghozi, Saiful (Journal of Rural Tourism, 2024)
We are delighted to announce the publication of the first issue of the Journal of Rural Tourism. This marks a significant milestone in our collective efforts to explore, understand, and contribute to the sustainable development of rural tourism around the world. This journal serves as a platform for academics, practitioners, and policymakers to share ideas, research findings, and best practices that highlight the richness and potential of rural destinations. As we celebrate this inaugural issue, we extend our heartfelt congratulations to all authors, reviewers, and the editorial team who have made this publication possible. In the future, this journal will introduce a diverse range of innovative studies, interdisciplinary approaches, and both global and local perspectives that are expected to enrich the discourse on rural tourism. We also hope the journal will become a vibrant space for dialogue, inspiration, and collaboration among all stakeholders. We look forward to continued partnerships and collective growth as we build a dynamic academic community in the field of rural tourism.